Analysis of Food consumed by Indonesian Moslem Hajj Pilgrims: Complete and Incomplete Nutrition - Alfiah, Alfiah; Hapsari, Rr. Ayu Fitri; Wulandari, Endah (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2023)
Background.The Mabrur hajj is the goal of carrying out hajj. Hajj pilgrims during the hajj journey are expected to have physical readiness besides financial and security. Health problems while in Mecca such as: congested congregation, population diversity, climate, and far from health facilities arises the possibility of various infections and non-infections. One of the physical readings is through the consumption of nutrients during the Hajj pilgrimage. This study analyzes the understanding of nutritional needs for health during the pilgrimage journey of IndonesiaMethods. The design of this study was conducted descriptively observing a quantitative approach by filling out a questionnaire. The number of respondents who filled out the questionnaire reached 231 people with the following profiles: 66% women; 71% of the productive age is 25-50 years.Results:There are 71% of respondents consuming food with incomplete nutritional composition at every meal. However, most of the nutritional composition consumed and needed has been fulfilled. There are only a few types of fruit that are less liked because they are not accustomed to the tongue of the pilgrims. There are 55% pilgrims who prepare their own supplements and medicinesConclusion: This shows the awareness of pilgrims to the need for macronutrients and micronutrients during the pilgrimage. It is necessary to educate the benefits of nutrition need to be done to reduce immunity, energy needs, physical health and religious approaches.